Future-Proofing HR: Embracing Change and Innovation in Human Resource Management - Djogo, Y. Ony (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study explores the relationships between Change Management, Innovation in HR Practices, Organizational Agility, and HR Effectiveness at PT Bandung Indah Gemilang. Utilizing a quantitative approach with random sampling of 70 employees, the research employed Smart PLS for data analysis. The results reveal that effective Change Management significantly enhances Organizational Agility, which in turn positively impacts HR Effectiveness. This underscores the importance of robust change management strategies in improving organizational agility and HR performance. However, while Innovation in HR Practices is positively associated with Organizational Agility, its indirect effect on HR Effectiveness through agility is not statistically significant. These findings highlight the critical role of change management and agility in driving HR improvements, while also suggesting that the current innovation strategies in HR may need further development to realize their full potential.